Implementation of Islamic Moderization in Mahasantri Al-Zamachsyari - Maulidina Nabila (Green Publisher Indonesia, 2021)
The Indonesian nation is a multicultural society with its plurality. Diversity includes differences in culture, religion, race, language, ethnicity, tradition and so on. In such a multicultural society, tensions and conflicts often occur between cultural groups and have an impact on the harmony of life. The purpose of this paper is to discuss religious moderation in diversity in realizing the peace of the Indonesian nation. The method used is qualitative research. The conclusion of this study is that multicultural life requires multicultural understanding and awareness that respects differences. It takes an attitude of religious moderation in the form of acknowledging the existence of other parties, having a tolerant attitude, respect for differences of opinion. The main influence of religious moderation in the digital space is finding its momentum. The counterbalance in question is a counter-narrative to create a substantive and essential religious framing, namely moderate and tolerant.